Factors influencing the Return Migration of Rural Youths in South India - Parameswaranaik J,; Jha, Sujeet Kumar; Manjunatha G . R, (Journal of Agricultural Extension Management, 2020)
Return migration is the voluntary movement of migrants back to their place of origin. It is the logical consequences of the successful achievement of all migrationrelated goals and targets. It is becoming a common phenomenon in rural India. Tamil Nadu, Karnataka and Kerala states were selected for the study. Total 180 respondents were investigated and the factors influencing the return migration were categorized into two groups viz, as push factors and pull factors. Low salary and non availability of better job are the most important push factors that influenced the rural youth to come out from the urban area with an RBQ value 84.69 and 78.26 respectively. To continue in family occupation (78.43) was most significant pull factor of return migration. Free in terms of decision making (71.10), to look after age old parents & join family members (68.56) were also significant pull factors responsible for return migration.The push and pull factors influencing the return migration of the rural youth should be considered while devising suitable extension interventions for programmes like ARYA and other youth programmes in agriculture and rural development